Sedentary time play a moderator role in the relationship between physical fitness and brain-derived neurotrophic factor in children: A pilot study - Camila Felin Fochesatto; Caroline Brand; Francisco Menezes; Carlos Cristi-Montero; Adroaldo Cezar Araujo Gaya; Neiva Leite; Anelise Reis Gaya (Journal of Exercise Science & Fitness, 2023)
Background/Objective: Despite some advances, there are many controversies concerning brain-derived neurotrophic factor (BDNF) and its relationships with variables related to physical fitness and sedentary time, especially in children. The aim of the study was to explore the moderating role of sedentary time on the association between physical fitness and BDNF. Therefore, this study will add to the perspective of understanding how much time children may spend being sedentary with no deleterious influence on the positive association between physical fitness and BDNF. Methods: This cross-sectional study included 44 children aged between 6 and 11 years (9.02 ± 1.43) from a public school in Porto Alegre, Brazil. Cardiorespiratory fitness (CRF) was determined by the 6-min walk/run test, and muscular strength was determined through the lower limb strength test (LLS). Sedentary time was assessed through accelerometers, and blood samples were collected to determine serum BDNF levels (z score). Moderation analysis was performed using the PROCESS macro adjusted for sex, age, somatic maturation, waist circumference, and socioeconomic level. Results: Sedentary time moderates the relationship between CRF and BDNF, such that children should spend less than 511 minutes per day sedentary to achieve the benefits of CRF in BDNF concentrations. Conclusion: Sedentary time plays a significant moderating role in the relationship between CRF and BDNF. Therefore, to promote brain health in children, both increasing physical fitness and reducing sedentary time might be encouraged.